Workation Phenomenon and Hotel Selection for Hotel Room Design Considerations - Fitriani, Anindita Dara; Maharani, Yuni (Gorga : Jurnal Seni Rupa, 2024)
This study explores the factors influencing hotel selection for workation. The term workation, derived from the combination of the words "work" and "vacation," refers to the trend of working while on vacation, which has emerged as a result of the Covid-19 pandemic. The workation trend is believed to enhance mental well-being and work productivity by balancing work life with everyday life. Workationers, with their unique characteristics, have preferences for how they conduct their workation. This study aims to analyze theories and literature regarding these preferences. The method used is a qualitative approach through a literature review based on reputable national and international scientific articles related to the topic. Based on findings from the literature review on workation work preferences and hotel selection, two intersecting factors were identified: room quality and room type. These two factors can serve as considerations for hotel management and interior designers in creating or developing hotel room designs. This study is expected to provide recommendations for designers and policymakers in addressing the needs of workation participants in the future.